Meningkatkan Minat Minat Belajar Al-Quran Pada Anak Dan Remaja Di Batang Arah Tapan - Efrinandi Saputra; Ahmad Khairul Nuzuli; Winda Oktaviana (AMMA : Jurnal Pengabdian Masyarakat, 2023)
Interest in learning the Quran in children and adolescents is important to be developed to ensure their love for religion and increase their spiritual understanding. This article aims to find out what causes low interest in learning the Koran in children and find solutions to increase interest in learning the Koran in children in Nagari Batang Arah Tapan. This research was conducted by interview method and direct observation at TPQ in Nagari Batang Arah Tapan. There are several factors found, namely internal factors and external factors. The findings of this study are expected to provide insights and guidelines for parents, teachers, and the community in Nagari Batang Arah Tapan to increase children's interest in learning the Koran.